Role of social capital in adolescents’ online gaming: A longitudinal study focused on the moderating effect of social capital between gaming time and psychosocial factors - Kim, Gyoung Mo; Jeong, Eui Jun; Lee, Ji Young; Yoo, Ji Hye (Frontiers in Psychology, 2022)
Adolescents often create social relationships with their gaming peers who take on the role of offline friends and peer groups. Through collaboration and competition in the games, the social relationships of adolescents are becoming broader and thicker. Although this is a common phenomenon in online games, few studies have focused on the formation and roles of social capital among adolescent gamers. In particular, longitudinal research that examines the role of social capital in terms of influencing gaming time on adolescent gamers' psychosocial factors has been minimal. This study was designed to fill this gap to see the long-term effect of social capital among adolescent gamers. Specifically, by using the three-year longitudinal data involving 403 adolescents, we analyzed the effect of gaming time on psychological factors (i.e., loneliness, depression, self-esteem, and life satisfaction) with the moderating role of social capital. Results showed that social capital played a crucial moderating role. In the higher social capital group, gaming time enhanced the degree of self-esteem and life satisfaction. However, a vicious circle was found in the lower social capital group: gaming time increased the degree of depression but decreased self-esteem, which in turn led to increase in gaming time. These results indicate that games work as an important tool for social capital cultivation among adolescent gamers, which imply successful cultivation of social capital is a key to positive gaming effects. Theoretical and practical implications are discussed.